To eat or not to eat junk foods? Improvement in children’s intention to reduce junk foods consumption following exposure to a media literacy intervention - Bicoy, Nino Daryll; Gravoso, Rotacio S. (Annals of Tropical Research, 2022)
Exposure to junk food information leads to high junk food consumption among children. This situation has raised concerns among agencies and organizations mandated to ensure children’s health because high junk foods consumption results in several health problems. This study aimed to ascertain the effects of a media literacy intervention on elementary school children’s knowledge, attitude towards junk foods, subjective norm, perceived behavioral control, and intention to eat junk foods and consume junk foods. Treatment groups included analysis+analysis, analysis+production, and no intervention. Children who underwent the analysis+production approach had significantly higher improvement in their attitude, subjective norm, perceived behavioral control, and intention during the post-test and the delayed post-test than those in the analysis+analysis approach and those not treated with any intervention. Results suggest that the analysis+production approach could improve children’s knowledge of junk foods’ health impacts and reduce their attitude towards eating junk foods, subjective norm, perceived behavioral control, and intention to eat junk foods. Overall findings indicate that initiatives aimed to encourage children to eat nutritious foods need repetition of the message. Aside from curriculum integration, engaging parents and application of game-based learning are also potential mechanisms for improving children’s food habits.